Mengatasi Kecanduan Media Sosial dalam Pernikahan: Peran Konselor Pastoral dalam Memperkuat Komitmen Pasangan - Asman, Fhilia; Rumate, Charga Jofial; Kalensang, Geby Ladesya; Makakombo , Feiby Paulin; Baraa, Fony; Semuel Selanno (PT. Giat Konseling Nusantara, 2024)
This study aims to explore the impacts of social media addiction on marriage, as well as the role of pastoral counselors in assisting couples to overcome such addiction and strengthen their marital commitment. Social media addiction can disrupt face-to-face communication, diminish the quality of shared time, and enhance feelings of detachment. Moreover, unrealistic social comparisons and online conflicts can erode trust and stability within marriage, even increasing the risk of divorce. Through a qualitative approach, this research will identify effective strategies and methods employed by pastoral counselors to address the negative impacts of social media addiction on marital dynamics. It is hoped that the findings of this study will provide profound insights into the importance of the pastoral counselor's role in supporting couples to overcome social media addiction and fortify their marital commitment.